Development of a device for detecting target specimens from EUS-guided FNA samples - Matsumoto, Kazuya; Ueki, Masaru; Takeda, Yohei; Harada, Kenichi; Onoyama, Takumi; Kawata, Soichiro; Ikebuchi, Yuichiro; Imamoto, Ryu; Horie, Yasushi; Murawaki, Yoshikazu (Endoscopy International Open, 2015)
Background and study aims: Specimens collected by fine needle are microscopic and contain blood; therefore, the presence of a target specimen within a sample is often difficult to confirm. Although rapid on-site evaluation (ROSE) during endoscopic ultrasound-guided fine needle aspiration biopsy (EUS-FNA) is beneficial, many health care facilities are unable to apply this technique due to a lack of cytopathologists. The aim of this study was to develop and validate a device that detects the target specimen within pancreatic tumor EUS-FNA samples. Patients and methods: Fifty-eight consecutive patients with solid pancreatic masses were studied for a preliminary case series at a tertiary-care university hospital (Tottori University Hospital, Yonago, Japan). The material collected was checked with a target sample check illuminator (TSCI) and was evaluated by one cytopathologist. Results: The agreement rate between the TSCI and histopathology was 93.7 %. Further testing procedures were not needed in 91.4 % of patients, and the mean number of needle punctures was 1.2 after a single pass using TSCI. No adverse events were encountered with the procedure.Conclusions: With the introduction of the TSCI in EUS-FNA, it became possible to both collect the minimum necessary target samples by EUS-FNA and to end further procedures, even without performing ROSE.